No -tillage seeder of fruit tree sylvan life green manure seed - SHUAI QIUYUE; ZHOU CHANGRONG; HOU SHILI; CHEN MIN; HUANG QINGQING; ZOU MEI; LYU CHAOYAN (2018)
The utility model discloses a no -tillage seeder of fruit tree sylvan life green manure seed, a large amount of seeds can be stored to this kind of seeder can need not add the seed for a long time, the degree of depth of convenient regulation seed whereabouts, it can sow only to need to promote the handspike, can pass through the planting depth of the depth control seed of control gauge wheel, theseed is followed grainbox entering seed metering ware and is followed under the drive of belt in the seed whereabouts mouthful entering litter wheel, the rotation of seed metering ware axis of rotation makes the seed fall down and discharge from the furrow opener through scraping kind of ware from seed nest eye, the press wheel can carry out simple flattening to the seed of following planting, broadcast the density of the speed control seeding that speed adjusting festival ware can slide adjusting seed whereabouts, and can add the pipe through fertilizer and add fertilizer, the furrowing blade is convenient for loose